Adjustment Speed of the Capital Structure in the Telecommunication Industry in Indonesia Year 2013-2018 - Putra, Fikri Dzuraeka; Hendrawan, Riko (International Journal Labs, 2023)
In 2013, telecommunications companies in Indonesia relied significantly on debt loans as a source of funding, with an average capital structure of -11.51%. The highest increase was observed in 2015, reaching an impressive 99.20%. Given this fluctuation, it becomes imperative to conduct research focusing on the adjustment speed of the capital structure in telecommunications companies during the period from 2013 to 2018. The research findings indicate varying rates of adjustment in capital structure, particularly in terms of Debt Equity Ratio (DER). The fastest adjustment was seen in XL Axiata at -19.14% and Indosat at -1.62%, while Telkom Indonesia exhibited a slower adjustment rate at 36.72%, and Smartfren Telecom had the slowest adjustment at 51.96%. Similarly, when considering the Debt Asset Ratio (DAR), XL Axiata displayed the swiftest adjustment at -17.63%, followed by Telkom Indonesia at -9.05%, and Indosat at -3.11%. In contrast, Smartfren Telecom had the most gradual adjustment, with a notable value of 71.70%. These findings underscore the dynamic nature of capital structure in the Indonesian telecommunications sector during the specified period. The varying speeds of adjustment in debt ratios reflect the strategic financial decisions made by these companies in response to market conditions and internal factors. Further analysis is essential to comprehend the factors influencing these diverse adjustment rates and their implications for the industry's financial stability.